Valstybiniai perversmai Baltijos šalyse (1926 ir 1934 m.): panašumai ir skirtumai - Butkus, Zenonas (Lietuvos istorijos studijos, 2006)
The article compares the political upheaval that took place in Lithuania 80 years ago with those staged in Estonia and Latvia in 1934. Their similarities and differences are discussed, and their historiography is compared. All the three were classified as military-political coups that caused transition from democratic to an authoritarian ruling system without changing socio-economic system or foreign policy. The main alleviating circumstance common to the coups in the Baltics was disproportionate domination of legislative power over the executive in the period after the First World War. The alternatives of power distribution are discussed, employing the Finnish model of democratic system, according to which the parliamentary power is outweighed by the stronger institution of President. The model enabled a more flexible reaction to the danger of extremist trends or serious blows to democracy; it also contributed to the protection from damaging impact of outward influences, which was especially noticeable in Estonia. The differences in the coups in the Baltic states are connected with the differences of the time and circumstances, as socio-economic conditions were different in 1926 and 1934 (the Great Depression and its consequences in Latvia and Estonia, while only a local crisis was experienced by Lithuania). The international situation was different as well: growing activity of the right-wing radicals after fascists took power in Germany and consolidation of Stalin’s dictatorship in the USSR. The most significant difference is thought to lie in the fact that the 1926 coup was directed against the reforms that were planned or undertaken by the left-wing coalition, while the 1934 political upheavals attempted to prevent a possible takeover by the right-wing extremists, though some data can be found that by means of a coup K. Ulmanis was also interested in removing Social Democrats—the strongest political party in Latvia—from their path to power. The coups were different in their technique as well. The government was overthrown only in Lithuania, while in Latvia and Estonia those in power consolidated their position even more, i.e. being in possession of a part of the democratic power, seized it all and turned it into authoritarian. However, the democratic systems were destroyed in all the Baltic States, thus, the lessons learnt should stay in our heritage and cultural memory. Three aspects of the approach to the coup are being developed in recent Latvian historiography. Aivars Stranga (earlier partly Edgars Dunsdorf) and some other researchers mainly from the University of Latvia deny the validity of the objective prerequisites of the upheaval. Meanwhile, Karlis Ulmanis’ strive for authoritarian power and the political short-sightedness of the Social Democrat leaders is being emphasized. Antonij Zunda would like to find more thorough analysis and less criticism in the evaluation of the coup. The scientists from the Institute of History of Latvia tend to focus their attention on the analysis of the prerequisites of the coup, even admitting that the coup was inevitable. Neither in Estonian nor in Lithuanian historiography can the above trends be observed; critical analysis of the coup is prevailing in both.